Parámetros físico - químicos y microbiológicos en la calidad ambiental del Río Nanay en Iquitos, Loreto – 2024 - Reaño Elaluf, Sarai Shantal (2025)
The objective of this study was to analyze the environmental parameters of the Nanay River water in 2024. Its approach was quantitative, prospective, simple descriptive, and non-experimental. The sample was defined by monitoring conducted during the low and high-water periods. Inclusion and exclusion criteria were taken into account. The technique was measurement, and the instruments used were thermometers, black throat, etc. The data was processed and tabulated with Excel and then processed through Python software using the Julius artificial intelligence platform. The monitoring results indicate that the water temperature of the Nanay River during the flood period exceeds the permitted environmental limit, The pH, electrical conductivity and total suspended solids remain within the ranges established by national regulations, the high values of Biochemical Oxygen Demand (BOD₅) show a significant load of biodegradable organic matter, which represents a risk to the oxygenation of the river and could be related to urban discharges without adequate treatment, the levels of fecal coliforms in both hydrological periods were well below the regulatory limit established by DS 004-2017-MINAM, which indicates a favorable sanitary condition and a low load of recent fecal contamination in the evaluated section of the Nanay River, it is recommended to implement a continuous monitoring system in the sections of the Nanay River exposed to urban growth, with emphasis on the detection Early detection of domestic or industrial discharges that could increase the organic load (BOD₅) of the water body.